Rethinking risk management : critically examining old ideas and new concepts - Nason, Rick (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2017)
Risk management has become a key factor of successful organizations. Despite risk management's importance, outdated and inappropriate ideas about how to manage risk dominate. This book challenges existing paradigms of risk management and provides readers with new concepts and tools for the current dynamic risk management environment. This book has two major origins: The first is a series of executive workshops that I have been conducting for the last several years for a major international company. The second origin is an innovative and popular course on enterprise risk management that I have developed and delivered for MBA students. The book reflects these two origins in that it covers both the current base of risk management knowledge but critically examines that base by exploring emerging risk management ideas and concepts. The framework for the book is a series of questions that allows for an interesting and thought-provoking look at current ideas and forward-looking concepts. This book, intended for senior managers, directors, risk managers, students of risk management, and all others who need to be concerned about risk management and strategy, provides a solid base for not only understanding current best practice in risk management, but also the conceptual tools for exploiting emerging risk management technologies, metrics, regulations, and ideas. The central thesis is that risk management is a value-adding activity that all types of organizations, public, private as well as not-for-profit, can use for competitive advantage and maximum effectiveness.
1. What is risk? -- 2. Have we lost the plot? -- 3. What is complexity? -- 4. What causes risk? -- 5. Are risk frameworks evil? -- 6. Does risk management add value? -- 7. Should risk management be based on process or judgment? -- 8. How do you create a great risk culture? -- 9. Is your risk management too good? -- 10. What is the future of risk management? -- Index.
Includes bibliographical references and index.
Title from PDF title page (viewed on March 9, 2017).
Keywords: Risk management; ambiguity; complexity; decision making; enterprise risk management; hedging; management of complexity; regulation; risk management; risk mitigation; strategic analysis; uncertainty; volatility; VUCA; Libros electronicos